ANALYSIS OF ABNORMAL RETURN AND TRADING VOLUME ACTIVITY BEFORE AND AFTER THE BINOMO CASE ON STOCK PRICE OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ita Kurnia Dewi; Indra Lila Kusuma; Desy Nur Pratiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to determine whether there was a difference in the average abnormal return and trading volume activity between before and after the Binomo case, and whether there was a difference in the average abnormal return and trading volume activity between before and after the information that Indra Kenz was named a suspect. Data are collected and analyzed using descriptive statistical test dan normality test. Method of hypothesis testing by paired sample t-test. The results obtained from this study indicate (1) there is no difference in the average abnormal return between before and after the Binomo case, (2) there is no difference in the average trading volume activity between before and after the Binomo case, (3) there is no difference the average abnormal return between before and after Indra Kenz was named a suspect, (4) There was a difference in the average trading volume activity between before and after Indra Kenz was named a suspect